MICRO SMALL MEDIUM BUSINESS DEVELOPMENT STRATEGY IN INCREASING THE WELFARE OF THE PEOPLE OF KEMLAGILOR TURI LAMONGAN VILLAGE DURING THE COVID-19 PANDEMIC - Rohma Zulia Budiarti; M. Rizal Nur Irawan; Ike Susanti (Jurnal Scientia, 2022)
During the Covid-19 pandemic, the MSME sector became a sector that made a major contribution to the Indonesian economy. Since the pandemic, MSME actors, especially in the Kemlagilor Turi Lamongan village area, have been faced with various challenges that have come. This requires MSME actors to form a strategy to develop their business in the midst of the Covid-19 pandemic as is currently happening. This study aims to determine the development strategy of Micro, Small and Medium Enterprises using SWOT analysis. The sample used was 20 MSME business actors. The data analysis method used is descriptive qualitative research method with analytical tools in the form of SWOT and TOWS analysis. From the results of the study it can be seen that the most influential strategy in improving the welfare of the Kemlagilor Turi Lamongan village community is the SO ( strength-opportunity ) strategy.